1997
DOI: 10.1111/j.1365-2621.1997.tb03982.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Alkaline Degradation of the Food Pigments Curcumin and Curcuminoids

Abstract: Alkaline degradation of the pigments curcumin (CC), demethoxycurcumin (DMC) and bis-demethoxycurcumin (BDMC) in aqueous solutions of purified and commercial oleoresin sources was investigated. Alkaline degradation of the compounds corresponded to pseudo-first-order kinetics. Responses were similar for pigments combined or alone in solutions. Profiles of rate constants were closely associated to polynominal curves. Degradation rate constants rapidly increased from pH 7.45 to a maximum at about 10.2 and then ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 11 publications
(10 reference statements)
0
41
0
3
Order By: Relevance
“…Curcumin application in aqueous solution is limited to the basic pH range. 9,10 Curcumin solubility can be increased by chemical modification or derivatization, such as complexation or interaction with macromolecules, surfactants and copolymers. 11 The spray drying technique represents a good alternative to obtain a soluble system for the industrial application of curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin application in aqueous solution is limited to the basic pH range. 9,10 Curcumin solubility can be increased by chemical modification or derivatization, such as complexation or interaction with macromolecules, surfactants and copolymers. 11 The spray drying technique represents a good alternative to obtain a soluble system for the industrial application of curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found pseudo-zero-order kinetics of curcumin decomposition when working in unbuffered aqueous medium of pH 10 -13.5, with a rate constant of 1.39 10 -9 M/min [150]. A recent study showed firstorder kinetics of degradation for curcumins I, II and III, where phosphate, borate, Tris and carbonate buffers were employed [153]. Curcumin III (bisdemethoxycurcumin) was the most stable, with a rate order of I > II > III.…”
Section: H Hatcher Et Al a Critical Review Of Curcuminmentioning
confidence: 99%
“…146 Whilst HPLC is the most common technique used for the determination of curcumin, the separation and individual quantitation of the three curcuminoids is important because their extinction coeffi cients and stabilities vary. [147][148][149] Additionally, when used in combination with annatto, the isomers of the yellow-coloured thermal degradation products of annatto exhibit similar chromatographic behaviour to the curcuminoids. Since the curcuminoids are not currently readily available as pure reference materials they normally require preparation from turmeric extracts, which is very time consuming.…”
Section: Dicinnamoylmethane Dyesmentioning
confidence: 99%